PENGELOLAAN SISTEM INFORMASI MANAJEMEN PENGADAAN DAN PENGHAPUSAN PERALATAN KANTOR DI KOMISI PEMILIHAN UMUM LOMBOK BARAT - Comala Hikmi, Henni; Yansirus Saniyah, Eluiz; Puspitasari, Vina (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
This research aims to examine and analyze the management of Management Information System (MIS) in the procurement and disposal of office equipment at the Office of the General Election Commission (KPU) of West Lombok. Procurement and disposal of office equipment are crucial aspects in maintaining the efficiency and effectiveness of an organization's operations. However, their management can be complex, especially when involving the management of accurate and timely information. Using a qualitative approach, this research will analyze the processes of procurement and disposal of office equipment at the KPU of West Lombok and apply effective information management concepts and principles. The research methods used include interviews with relevant staff, direct observation, and analysis of related documents. The results of this research are expected to provide valuable insights for the KPU of West Lombok in improving the management of Management Information Systems related to the procurement and disposal of office equipment